2018
DOI: 10.1590/1983-21252018v31n311rc
|View full text |Cite
|
Sign up to set email alerts
|

USE OF ATMOSPHERIC PLASMA IN GERMINATION OF Hybanthus calceolaria (L.) Schulze-Menz SEEDS

Abstract: -Plasma technology is a fast, cost-effective, and pollution-free method that can be used in place of conventional methods to overcome seed dormancy. The goal of the present study was to determine the effect of different application times of atmospheric plasma on soaking and germination of Hybanthus calceolaria seeds in order to accelerate these processes. Helium plasma jet produced by dielectric barrier discharge was used to treat H. calceolaria seeds with applications of 1, 5, and 10 minutes. The treated seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…These seeds, from 48 h, kept the surfaces of their coats more hydrophobic, with lower contact with water and lower and slower imbibition, which reduced the amount of leachates released to the soaking solution. Results similar to that found here were verified by Silva et al (2018), with Hybanthus calceolaria seeds treated with atmospheric plasma for different periods of exposure and imbibition. Assessing the adequacy of the conductivity test, Araújo et al (2022) observed that the release of exudates increased as the seeds were imbibed.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These seeds, from 48 h, kept the surfaces of their coats more hydrophobic, with lower contact with water and lower and slower imbibition, which reduced the amount of leachates released to the soaking solution. Results similar to that found here were verified by Silva et al (2018), with Hybanthus calceolaria seeds treated with atmospheric plasma for different periods of exposure and imbibition. Assessing the adequacy of the conductivity test, Araújo et al (2022) observed that the release of exudates increased as the seeds were imbibed.…”
Section: Resultssupporting
confidence: 89%
“…This indicates that plasma, in all exposure times evaluated, reduced the contact angle of the seeds with the water drops, increasing their wettability. With the increase in the time of exposure to plasma, the composition of the outer layer of the seed coat may undergo chemical modifications, at the level of dysfunctions of functional groups, capable of altering the hydrophobic profile of the seed coat and, eventually, promote increased water absorption according to Silva et al (2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical factors may have a positive effect on physiological processes occurring in plants as well as in plant seedlings. The positive effect of plasma on the processes occurring in seeds is known [168][169][170]. Ways of accelerating new root formation are also still being sought.…”
Section: Plasmamentioning
confidence: 99%
“…Atmospheric plasma also appears in literature as a skin hydrophilicity facilitator [12], and this could be used in the pre-cosmetic facial procedure for the cosmetic skin hydration. The use of cold plasma has facilitated the permeation of various substances (nanoencapsulated or not) in several scientific experiments [2,[13][14][15][16].…”
mentioning
confidence: 99%